Biscuit joinery [ build a bookcase - Klausz, Frank (A fine woodworking DVD workshop, 2006)
Takes viewers through building and finishing a bookcase wall unit using biscuits. Also explains how to plan wall units, design drawers, doors, and shelves, choose the right kind of plywood, cut sheetgoods on the tablesaw, make a simple biscuit joinery fence, use knockdown hardware, edge plywood, and glue and assemble a bookcase.